Legal Aspects of BUMDes as Drivers of Village Economy: Aspek Legal BUMDes sebagai Penggerak Perekonomian Desa - Darodjat, Rafan; Harrieti, Nun (Lembaga Dongan Dosen, 2025)
Indonesia has a system of governance below the sub-district level, namely the urban village (kelurahan) and rural village (desa). The state's commitment to granting a formal position to village communities began with the enactment of Law Number 6 of 2014 concerning Villages and the establishment of the Ministry of Villages in 2014. The role of villages in managing their territories not only supports inclusive community participation but also enables Village Governments to engage in business development through Village-Owned Enterprises (BUMDes). The establishment and management of BUMDes are closely related to legal aspects such as legal standing (legalitas), business operations, management structure, business aspects, and other relevant factors that require thorough study to ensure proper governance of BUMDes. The method used in this community service activity is normative juridical, implemented through partnerships. The study employs a Systematic Literature Review (SLR) method, utilizing previous research as problem-solving references.The results of this study indicate that village governments have advantages in governance because they possess village land that can be managed for the welfare of the community. This management can be carried out by BUMDes. For example, BUMDes Bumiwangi manages the Bukit Cula Tourism Area, where the profits can be used as village revenue, create employment opportunities, and improve the community's economy. The operation of BUMDes must, of course, have legal legitimacy. This community service establishes partnerships to fulfill legal requirements covering establishment, operational activities, and business contract aspects.